A cross-sectional study of facial index in Western Uttar Pradesh population between 18-25 years of age - Vangara, Shanmukha Varalakshmi; Kumar, Dhananjay; Arora, Neel Kamal (Asian Journal of Medical Sciences, 2021)
Background: Facial anthropometry is the scientific study of measurements and proportions of the human face. There is huge paucity in the metric measurements of face in Indian population. This study is involved in collecting facial anthropometric data of Western Uttar Pradesh population of age group between 18-25 years. Aims and Objectives: This study aims at evaluating predominant facial phenotype, using facial height and facial width of Western Uttar Pradesh population as study subjects. Materials and Methods: The study was conducted on 200 medical and paramedical students of Shri Ram Murti Smarak Institute of Medical Sciences (SRMS-IMS), Bareilly, Uttar Pradesh. The study subjects were of 18-25 year’s age, belonging to Western Uttar Pradesh region. Digital Vernier Caliper was used to measure the facial parameters. The data was analyzed using statistical tool SPSS 16.0 version. Results: In the present study it is found that facial height and width are more in males compared to females. This difference is statistically significant. On analyzing facial index, hyperleptoprosopic face is the predominant phenotype in males as well as in females, followed by leptoprosopic type in males and mesoprosopic type in females. However, gender differences in facial index are not statistically significant at p<0.05. Conclusion: The current study reveals that facial parameters can be used to determine the gender of an individual on the basis of height and width.